Governing America : The Revival of Political History - Zelizer, Julian E. (Book collections on Project MUSE., 2012)
In recent years, the study of American political history has experienced a remarkable renaissance. After decades during which the subject fell out of fashion and disappeared from public view, it has returned to prominence as the study of American history has shifted its focus back to politics broadly defined. In this book, one of the leaders of the resurgence in American political history, Julian Zelizer, assesses its revival and demonstrates how this work not only illuminates the past but also helps us better understand American politics today.